The Effect of Drilling Exercise using N and V Model to Improve Forehand Clear Technique for Badminton Beginner Players - Nurman Hasibuan; Firmansyah Dlis; Ramdan Pelana (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
This study aims to determine the effect of drilling exercise using N and V model on increasing the forehand clear technique for badminton beginner players. This study uses an experimental method. A sample of 26 people is taken by using purposive random sampling from 38 total of population. The results show that there is an effect drilling exercise using N and V model on increasing the forehand clear technique for beginners. Furthermore, there is a difference in the effect of drilling exercise using N and V model on increasing forehand clear technique for beginners. It means that the drilling exercise using N model is better than the V model to improve forehand clear technique for badminton beginner players.